An IoT-Based Intravenous Fluid Measuring Device Using ESP32 and Ultrasonic Sensor - Redha, Umalbanen Sajad Abbas; Salman, Rawnaq Mahmood Abbas; Atiya, Tabarak Esam Abbood (Central Asian Journal of Medical and Natural Science, 2025)
Intravenous (IV) therapy plays a critical role in modern healthcare by enabling the direct delivery of fluids and medications into the bloodstream. Accurate monitoring of IV fluid levels is essential to ensure patient safety and prevent under- or over-dosing. This research presents the design and implementation of an IoT-based IV fluid measuring device that integrates an ultrasonic sensor, ESP32 microcontroller, LCD display, and relay module, connected to the Ubidots IoT platform. The system enables real-time monitoring of fluid levels, remote data visualization, and automated control of the infusion process. The experimental results demonstrate the effectiveness of the proposed device in accurately measuring fluid levels and transmitting the data to a cloud platform for continuous observation. This work provides a cost-effective, reliable, and scalable solution for enhancing patient safety in healthcare settings.